THE DEVELOPMENT STRATEGY OF THE NEW UZBEKISTAN IS IN THE PROCESS OF IMPLEMENTATION BRINGING FOREIGN ECONOMIC ACTIVITY TO HIGHER PEAKS AND THROUGH THIS ACHIEVING SUSTAINABLE ECONOMIC GROWTH (Multidisciplinary Journal of Science and Technology, 2023)
Measures such as further improvement of foreign economic activity and strengthening the integration of the national economy into international financial processes are of great importance in ensuring sustainable economic growth. The number of government programs adopted as part of the implementation of foreign economic activity in our country, the creation of economic benefits that can meet the requirements of competitive and international trade in the country, and the effective organization of export of these manufactured products are important tasks facing our country.